Tingkat Keterbacaan dan Keefektifan Kalimat pada Teks Tajuk pada Harian Fajar edisi Januari 2024 sebagai Sumber Bacaan Siswa SMA - Nesa Artika Dewi; Ainna Galuh Pratiwi; Monica Anggraini Choirunisa; Anggita Rahma Aprilianti; Cynara Rahmania; Asep Purwo Yudi Utomo; Muhajir Muhajir (Asosiasi Riset Ilmu Pendidikan Indonesia, 2024)
This research is to describe the readability and effectiveness of the Headline text in the January 2024 edition of Fajar Daily as a reading resource for high school students. This study aims to analyze the level of readability and effectiveness of sentences in the Headline text in the January 2024 edition of Fajar Daily. This research uses quantitative descriptive method. The data in this study are 14 Headline texts in the January 2024 edition of Fajar Daily which were collected using the data collection techniques of listening and noting and using the high method. The readability level was measured using Fry's Graph. The results showed that 7 texts were suitable for high school students' reading materials and 7 texts were not suitable for high school students' reading materials. In the analysis of the effectiveness of the Headline text on Fajar Daily January 2024 Edition, there are 14 texts. The results of this study can be used as an alternative reading source in schools for Indonesian language subjects, especially news text material at the high school level. This effectiveness analysis has two examples of effective sentences and four aspects found in ineffective sentences. The four aspects of ineffective sentences include word repetition, word selection errors, vagueness of meaning, and non-standardized words.